(untitled) (Security Dialogues, 2024)
This paper provides a detailed analysis ofwarfighting functions during the counteroffensive of the Ukrainian forces against Russian forces, as well as the efficiencyof warfighting functions, which has a significant impact on the results of the war. It will cover the period from the start of the counter-offensive of the Ukrainian forces, from June 2023, when some victories were recorded by the Ukrainian forces. Through the analysis and processing of confidential and already available information from social networks, media and the Washington Post, and in accordance with the comparison with the US doctrine, a special emphasis was placed on one of the warfighting functions in Ukrainian counter-offensive, that is, the system for combat service support.The method of analyses and synthesis was used to summarize the results and arrive at the conclusion. Hence it is confirmed that in terms of the organization and implementation of the combat service support warfighting function, the Ukrainian forces have failed to meet the right requirements in the right place and at the right time. The main culprit in all of this is the lack of sufficient time for preparation and training of personnel for different models of the same type of assets that were donated by Western countries during the war, as well as the rejection of US military officials’ advice to use frontal attack along one axis.